Unlocking Business Opportunities for Immigrants Returning to Their Home Countries - Ida Yulianti; Desi Tri Kurniawati; Wirawan Dony Dahana; Sri Palupi Prabandari; Didied Poernawan Affandy; Taufiq Ismail (IECON: International Economics and Business Conference, 2024)
This study aims to identify and analyze business opportunities available to immigrants returning to their home countries through a Literature Review approach. Returning immigrants bring valuable skills, capital, networks, and knowledge gained while living abroad, creating potential for starting and growing businesses in their homeland. Their international experience often allows them to recognize and capitalize on untapped market opportunities with a fresh perspective. Key factors that drive the success of these businesses include supportive economic conditions, newly acquired skills, stronger financial capital, and support from international business networks, providing access to broader markets and partnerships. However, these immigrants also face challenges such as cultural differences, complex business regulations, limited access to capital, and potential stigma or social discrimination. Economic, political, and social conditions in their home countries further influence the success of their ventures. Findings from this review offer valuable insights for governments and relevant institutions in formulating supportive policies for immigrant entrepreneurs, and inform future research exploring specific factors impacting the economic engagement of returning immigrants.